SK Current, Expressed During the Development and Regeneration of Chick Hair Cells, Contributes to the Patterning of Spontaneous Action Potentials - Levic, Snezana (Frontiers in Cellular Neuroscience, 2022)
During development and regeneration chick hair cells display spontaneous action potentials, which are exclusively sensitive to Ca2+. The role of this activity is unclear, but thought to be involved in establishment of proper synaptic connections and tonotopic maps, both which are instrumental to normal hearing. Using electrophysiological approach, this work investigated the functional expression of calcium-sensitive potassium (IK(Ca)) currents, as well as their role in spontaneous electrical activity in the developing and regenerating hair cells in chick basilar papilla. The main IK(Ca) in developing and regenerating chick hair cells is SK current, based on its sensitive to apamin. SK current functional expression showed most dramatic changes occurring at ~ E8-E16. Specifically, there is a developmental down-regulation of SK current after E16. The gating of SK current was very sensitive to availability of intracellular calcium, while showing very little contributions of T-type voltage gated calcium channels, which are one of the hallmarks of developing and regenerating hair cells. Additionally, apamin reduced the frequency of spontaneous electrical activity in hair cells’, suggesting that SK current participates in patterning hair cells’ spontaneous electrical activity.